Penguatan Literasi Membaca Dan Menulis Untuk Siswa Kelas Rendah SDN 02 Anggaraksa - Sabri, Muhammad; Husaeri, Husaeri; Azmi, Muhyidin; Jayadi, Ikbal; Rozana, Dira; Najihah, Firqatun; Thoibatun, Siti Zulpina; Faozan, Faozan; Ariwathan, Mutahhari; Hidayat, Romi; Riani, Rini Zakia Zulpa; Nurussoleha, Nurussoleha; Firdaus , M. Hilmi (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to strengthen reading and writing literacy in lower grade students at SDN 02 Anggaraksa, Pringgabaya District, East Lombok Regency. This research uses the Participatory Action Research (PAR) method with a problem solving approach. The research subjects were students in grades 1 and 2 of SDN 02 Anggaraksa. Observation results prove that the superiority of reading and writing literacy for lower class students in this school is still relatively low. Some of the problems found include students not knowing letters well, having difficulty distinguishing several letters, and their ability to compose simple sentences is still lacking. To overcome this, the service team applied the Edutainment method and picture and picture learning media in implementing the reading and writing literacy program. With the Edutaiment learning approach, it has been proven that progress has been made, such as creating interesting learning, students can focus more on learning and with the application of drawing and drawing learning media, students have more freedom in learning while playing. Activities are carried out for one month with four meetings each week, with a focus on letter recognition, spelling, learning while singing, and the use of visual media. Even though there are several obstacles such as a lack of reading facilities and infrastructure, this program has shown positive results in optimizing the interest and literacy abilities of lower grade students at SDN 02 Anggaraksa.